2021
DOI: 10.3390/su13063130
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture Land Use Change and Demographic Change in Response to Decline Suspended Sediment in Južna Morava River Basin (Serbia)

Abstract: This study expounds the dynamic relationships among agricultural land-use change, rural population migration, and sediment transport. The variability of suspended sediment load was detected by Mann–Kendall and Pettitt tests. From 1961 to 2007, the annual trend in suspended sediment concentration and sediment load demonstrated significant reduction (α = 0.001), with decreasing rates of 0.0144 g/L/y and 84.7 t/y, respectively. An abrupt change-point was detected in 1984 for the sediment load (p = 0.0001). The do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 61 publications
1
5
0
1
Order By: Relevance
“…The second factor of land use changes is also high index of the population aging. Later, Manojlović et al (2021Manojlović et al ( , 2022 demonstrated similar results in research for the Južna Morava river basin (A = 15,469 km 2 , comprising the Nišava watreshed) and for the Velika Morava river basin encompassing the Južna Morava river basin (A = 37,561 km 2 ). In both studies, it is shown that the decrease of rural population and areas of agricultural and arable land were directly related to the decline of suspended sediment.…”
Section: Introductionsupporting
confidence: 65%
“…The second factor of land use changes is also high index of the population aging. Later, Manojlović et al (2021Manojlović et al ( , 2022 demonstrated similar results in research for the Južna Morava river basin (A = 15,469 km 2 , comprising the Nišava watreshed) and for the Velika Morava river basin encompassing the Južna Morava river basin (A = 37,561 km 2 ). In both studies, it is shown that the decrease of rural population and areas of agricultural and arable land were directly related to the decline of suspended sediment.…”
Section: Introductionsupporting
confidence: 65%
“…The second factor of land use changes is also high index of the population aging. Later, Manojlović et al [4,5] demonstrated similar results in research for the Južna Morava river basin (A = 15,469 km 2 , comprising the Nišava watreshed) and for the Velika Morava river basin encompassing the Južna Morava river basin (A = 37,561 km 2 ). In both studies, it is shown that the decrease of rural population and areas of agricultural and arable land were directly related to the decline of suspended sediment.…”
Section: Introductionmentioning
confidence: 54%
“…Uzroci depopulacije u Srbiji su proučavani od početka 20. veka sa različitih aspekata, koji su povezani i mogu se klasifikovati i hronološki i prostorno. Među najznačajnijim se navode: agrarna prenaseljenost, ratovi i prisilne migracije, bolesti, promene granica, promene oblika vladavine, promene administrativnih jedinica, nacionalizacija imovine, emigracija mladog stanovništva, nepovoljna obrazovna struktura stanovništva, pad nataliteta, deagrarizacija, starenje stanovništva (Martinović & Ratkaj, 2015;Manojlović et al, 2021;Велојић & Радовановић, 2003;Мартиновић, 2004;Мартиновић & Шантић, 2006;Миливојевић et al, 2007;Милошевић et al, 2008;Milošević et al, 2010;Milošević et al, 2011;Babović, et al, 2016;Nikitović, 2019;Gatarić et al, 2022;Šabić et al, 2022;Gajić et al, 2022;Grupa autora, 2022;Ranković, 2023). Pomenuta naučna istraživanja ponudila su odgovore na pitanja zašto se sela prazne i do kakvih to posledica dovodi.…”
Section: Pregled Literatureunclassified